EVALUATION OF CHILDREN PROTECTION POLICY FROM VIOLENT ACTS IN SEMARANG CITY - Mustikasari, Nadia Ayu; Rostyaningsih, Dewi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2020)
ABSTRACT Semarang is one of the cities with a higher number of children's violence cases, to cope with this, the government of Semarang implementing the policy of child protection from violent acts. The purpose of this research is to evaluate and to describe how the policy is being held and the constraints faced with considering the indicators: institutional, financing, protection, cooperation and Partnerships, coaching and supervision. This research uses a qualitative descriptive approach. The informant determination techniques used are purposive sampling techniques and snowball sampling with data collection techniques through observation, interviews, and documentation. Analysis and interpretation of data using qualitative research data analysis techniques with the validity technique of source triangulation data. Results of the study showed that the implementation of child protection policy from violence in the city of Semarang has been done well but still less optimal because of some constraints including lack of human resources, Budget constraints, still less community participation, negative stigma from society, the difficulty of getting a school for violent victims, and not periodic supervision. The advice that can be given is: the addition of the number of members of the Board, the government must be more strict to the company to conduct CSR, need to prevent activities outside of formal education, need an increase in monitoring activities, need to A cooperative action from the school, and an increase in socialization activities.